Tutorial: Autonomic Nervous System - Craig Henkel (Association of American Medical Colleges, 2010)
Abstract Introduction There are few topics in anatomy more perplexing to first-year medical students than the autonomic nervous system. Given its complexity, this topic is amenable to approaches that may enhance student learning. In contrast to the web-based tools and technical support required with e-learning, the ability to create and deliver interactive tools with a common presentation software package can make innovative learning delivery methods, amenable to a broader base of instructors. We created an interactive learning PowerPoint tutorial for students to review prior to an anatomy lecture session. Methods As preparation for the first lecture on this topic, students may review this 25-minute PowerPoint tutorial. Be reviewing the basic objectives for the upcoming lecture, students arrive at the lecture with questions about what content is unclear and are prepared for more in-depth discussion. As a preliminary step in formally evaluating effectiveness of the interactive tutorial for student comprehension of the autonomic nervous system, results from two consecutive medical classes on a bank of standardized questions used as a part of the summative exam were compared retrospectively. Results When comparing the first round of standardized questions, the class given the interactive tutorial scored slightly higher on discriminative questions than the class with only the lecture presentation. There was no difference in performance for the two groups on competency questions. Further, instructors noticed a greater ease in communicating complex concepts of the autonomic nervous system when students had already begun to think about the anatomy and function of the system through the use of the interactive tutorial. Student feedback about this resource has been informal but the responses have been positive. Discussion The combination of an interactive learning tutorial with a lecture content in a blended learning approach has been favorably received by the students. The interactive format is engaging, complements traditional textbook reading assignments, and allows the lecturer to emphasize more difficult concepts while building on fundamental vocabulary and general principles, thereby decompressing the lecture hour. Furthermore, once the learning object is created it can be applied across a variety of instructional settings. For instance, learning objects created for the undergraduate medical education curriculum can be easily transferred for use in continuing medical education without additional preparation time and made accessible for asynchronous learning. Positive experiences with a familiar presentation format may stimulate creative learning approaches that subsequently propel faculty to explore more advanced technologies.